(untitled) (Prilozi za orijentalnu filologiju, 2017)
This paper consists of two parts: a short introduction about biography and the national idea of Sati al-Husri, who was one of the founders of modern Arab nationalism, and a translation of three chapters of his book Classes about formation of the National Idea (Kairo, 1951), refering to the national idea and the creation of the national states in the Balkans: Bulgaria, Yugoslavia and Albania. Proceeding the fact that Sati al-Husri was a witness of some important events in the period of almost ten years of his employment in the Balkans at the begining of this century and his interesting observations about the formation and the development of the national idea among the people of Bulgaria, Yugoslavia and Albania in the period of weakness of the Ottoman Empire, we should emphasize actuality and importance of his reflections compared with the new social and political conditions in these areas. It is noticeable in the translated fragments that al-Husri emphasized the role of language and religion in forming the nations, the specifies of Bulgaria and Yugoslavia as a common area for several nations, the judgment and the assumptions for the formation of the national selfconsciousness among the Albanians where sometimens we can notice some exaggerated simplifications under the influence of Fichte's ideas about the role of the language in forming the nations. But, in this form this paper is also interesting as an impulse for the study of the questions related to the national idea in the Balkans with respect to a series of factors which affected the current social-politic situation in this area.